FASED: A Framework for Data Ecosystems Health Evaluation - B. Lima, Glória de Fátima; S. Oliveira, Marcelo Iury; Farias Lóscio, Bernadette (Journal of Information and Data Management, 2022)
The growing availability of data in digital media has contributed to the creation of a large number of data ecosystems. However, having successful Data Ecosystem is still a challenge. In order to prevent the failure of a Data Ecosystem and ensure its survival, evaluating its health becomes fundamental. In a general way, the health of a Data Ecosystem can be defined as its ability to grow and survive over time. Indicators such as productivity, robustness, niche creation and sustainability can be employed to evaluate the health of a Data Ecosystem. In this paper, we propose a framework for data Ecosystem health evaluation composed of a set of indicators and metrics, which assess the Data Ecosystem’s current state and its ability to stay healthy over time. The results obtained when using the proposed framework offers evidence to assist in decision making on how data has being published and consumed in a Data Ecosystem, as well as to evaluate which ecosystems are more prosperous or need more investments.